A Visible Colorimetric Fluorescent Probe for Hydrogen Sulfide Detection in Wine - Haitao Chen; Xiaoming Wu; Shaoxiang Yang; Hongyu Tian; Yongguo Liu; Baoguo Sun (Journal of Analytical Methods in Chemistry)
A new efficient and practical fluorescent probe 6-(benzo[d]thiazol-2-yl)naphthalen-2-yl-thiophene-2-carboxylate (probe 1) was synthesized to detect hydrogen sulfide (H2S). The addition of H2S caused the solution of probe 1 to change from colorless to yellow, and the solution of probe 1 changes to different colors with respect to different concentrations of H2S. Importantly, probe 1 could help detect H2S efficiently by a distinct color response as a visible detection agent. Probe 1 reacted with various concentrations of H2S (0–200 μM), and the detection limit for H2S was 0.10 μM. Particularly, probe 1 can be applied as a sensor to detect H2S accurately in wine samples.